2008
DOI: 10.1080/00220380802242453
|View full text |Cite
|
Sign up to set email alerts
|

Robbing the Riches: Capital Flight, Institutions and Debt

Abstract: Capital flight undermines economic growth and the effectiveness of debt relief and foreign aid, and sometimes drains more resources from poor countries than does debt service. In an analysis of a large panel of developing and emerging market countries using annual data for 1970-2001, we show that both institutions and macro policies robustly affect capital flight. Our study also supports the existence of a revolving door relationship between debt and capital flight. More notably we find countries with weak ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
0
41
0
5
Order By: Relevance
“…A large and unmanaged public debt might cause debt overhang; macroeconomic instability; results in price volatility; and blocks capital inflows and encourages capital flight (Krugman, 1988;Alesina and Tabellini, 1989;Singh, 2006;Cerra et al, 2008;Malone, 2010). Again, Mohammed et al (2013) observed that debt servicing consumes a large share of government revenue thereby weakens government efforts in providing basic facilities in a country.…”
Section: Theoretical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large and unmanaged public debt might cause debt overhang; macroeconomic instability; results in price volatility; and blocks capital inflows and encourages capital flight (Krugman, 1988;Alesina and Tabellini, 1989;Singh, 2006;Cerra et al, 2008;Malone, 2010). Again, Mohammed et al (2013) observed that debt servicing consumes a large share of government revenue thereby weakens government efforts in providing basic facilities in a country.…”
Section: Theoretical Issuesmentioning
confidence: 99%
“…Meeting debt obligations continues to pose a threat to growth and development of Nigeria since paying it means sacrificing welfare and capital projects for social and economic development. The available empirical studies on the effect of debt on economic growth in various countries produced mixed findings and inconclusive results (Cerra et al, 2008;Malone, 2010;Reinhart and Rogoff, 2010a;Sefdari and Mehrizi, 2011).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…10 In the empirical literature, both capital flight and cumulative capital flight are examined. For instance, Boyce (1992), Cerra et al (2008), Fedderke and Liu (2002); Le and Zak (2006); Lensink et al (2000); Mikkelsen (1991), Ndikumana and Boyce (2003) and Pastor (1990) examined capital flight, while Cheung and Qian (2010), Collier et al (2001), Cuddington (1987), Dooley (1988) and Rojas-Suarez (1990) While equation (4) presents the essential spirit of the portfolio balance approach, it sidesteps the effects of other factors that influence capital movements. To properly assess the CID effect, we add control variables to (4) and consider the augmented regression…”
mentioning
confidence: 99%
“…Kadar pertumbuhan kredit domestik boleh memberi kesan kepada aliran kewangan haram melalui dua cara. Pertama, Cerra et al (2008) Pemboleh ubah bersandar dalam kajian ini adalah aliran kewangan haram. Menurut GFI, aliran kewangan haram merangkumi modal yang asalnya diperolehi daripada perniagaan yang sah seperti berdasarkan keuntungan dan sebagainya, tetapi ia dipindahkan ke luar negara secara haram iaitu melanggar undang-undang yang ditetapkan seperti tiada bayaran cukai korporat atau melanggar peraturan kawalan pertukaran.…”
Section: Kajian Lepasunclassified